Cyber Notary Kepastian Hukum Penyimpanan Dokumen Notaris - Selviany; Rizkianto, Kus; Rahayu, Kanti; Mukhidin, Mukhidin (Universitas Pancasakti Tegal, 2022)
Over time the conventional system will shift and be replaced with an electronic system, and the Notary Institution will slowly have to begin to adjust, especially in the UUJN-P the changes regarding cyber notary are only stated in the explanation of Article 15 Paragraph (3) and only to the extent that the authority to certify transactions electronically has not yet reached the concept of notary protocol storage thinking which is very possible to be carried out electronically with the aim of security and the effectiveness of notary protocol storage. This study aims to: 1) Describe the legal arrangements regarding Cyber Notary; 2) legal certainty of the retention of notarial documents with cyber notary. This study uses a library research method with a normative research approach with qualitative analysis, which describes various arrangements regarding Cyber Notary and legal certainty of notarial document storage. The finding is that the new UUJN-P regulates transactions carried out electronically, but there is no provision on the storage of original minuta deeds and warkah electronically. However, cyber notary The ITE Law in general has regulated the electronic storage of archives or documents although there are no specific rules that list or mention notarial documents or archives. Article 1 number 4 of the ITE Law Amendment states that: